2021
DOI: 10.1002/ajpa.24266
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic diversity of Cebuella in the western Amazon: Molecular, morphological and pelage diversity of museum and free‐ranging specimens

Abstract: Objectives We investigated the diversity of the pygmy marmoset, Cebuella pygmaea, by comparing genetic, morphological and pelage traits of animals from Peru and Ecuador. Materials and Methods We extracted DNA from museum specimen osteocrusts and from fecal samples collected from free‐ranging individuals. We sequenced the mtDNA cytochrome b gene and the control region from samples collected at 13 different sites and used Bayesian inference and Maximum Likelihood to identify distinct clades. We took measurements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 23 publications
(44 reference statements)
5
13
0
Order By: Relevance
“…By placing these data in the context of available cyt b mitochondrial barcode gene sequences from pygmy marmosets across their distribution, we provide the first range-wide phylogenetic analysis of this taxon and confirm the correct naming of the two species of Cebuella , thereby resolving the present taxonomic uncertainty. We also re-evaluate the current geographical distribution hypothesis for the two Cebuella species ( Mittermeier et al, 2013 ) based on our results and those of Porter et al ( 2021 ).…”
Section: Introductionmentioning
confidence: 60%
See 4 more Smart Citations
“…By placing these data in the context of available cyt b mitochondrial barcode gene sequences from pygmy marmosets across their distribution, we provide the first range-wide phylogenetic analysis of this taxon and confirm the correct naming of the two species of Cebuella , thereby resolving the present taxonomic uncertainty. We also re-evaluate the current geographical distribution hypothesis for the two Cebuella species ( Mittermeier et al, 2013 ) based on our results and those of Porter et al ( 2021 ).…”
Section: Introductionmentioning
confidence: 60%
“…The morphological analyses of Garbino et al ( 2019 ) and Porter et al ( 2021 ) identified the Napo River as the southern range limit of C. pygmaea in Peru and Ecuador. Previously, it had been thought that the divide was marked by the Amazonas-Marañón rivers, extending west to the left bank of the Pastaza River ( Mittermeier et al, 2013 ; van Roosmalen & van Roosmalen, 1997 ).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations